Improved Oxidation Stability of Camellia Oil-in-Water Emulsions Stabilized by the Mixed Monolayer of Soy Protein Isolate/Bamboo Shoot Protein Complexes - Xi, Yuhang; Zhang, Aiping; Wang, Zhongjiang; Farooq, Shahzad; Zhang, Cen; Wu, Liangru; Zhang, Hui (Frontiers in Nutrition, 2021)
The complex of soy protein isolate (SPI)/bamboo shoot protein concentrate (BPC) was developed to stabilize camellia oil-in-water (O/W) emulsions. The surface hydrophobicity of the BPC/SPI complex driven by hydrogen bonds and electrostatic attractions was improved. With the increasing ratio of BPC in the complex, the tighter network layer structure of complex was formed due to the rearrangement of proteins, and the emulsions showed a progressive enhancement in the gel-like structures. At the SPI/BPC ratio of 2:1, the emulsions had smaller droplet size and lower creaming index of 230 nm and 30%, and the emulsifying activity and stability indices of the emulsions were 803.72 min and 11.85 g/m2, respectively, indicating the better emulsifying activity and stability of emulsions. Meanwhile the emulsions stabilized by the complex at the ratio of 2:1 showed better storage and antioxidant stability. These findings are expected to develop the application of bamboo shoot in the emulsion-based food products such as mayonnaise, salad dressings, and sauces.